The clinical case of use of extracorporeal hemocorrection methods in a female patient with refractory arterial hypertension. Case report - А. А. Agadzhanyan; N. T. Khachatryan; O. А. Sivakova; A. А. Sokolov; I. E. Chazova (Терапевтический архив)
The particular focus of the modern scientific community and practical medicine is concentrated on patients with refractory arterial hypertension when appropriate lifestyle measures and treatment with optimal or best tolerated doses of 5 or more drugs with diuretic and mineralocorticoid receptor antagonist fail to lower office blood pressure to 140/90 mmHg. Inefficiency of recommended treatment methods requires new therapeutic approaches for these patients. The efficiency and mechanisms of extracorporeal treatment for blood pressure reduction in patients with malignant hypertension were first studied in the 1980s and 1990s. This clinical case study demonstrates the use of extracorporeal hemocorrection procedures as part of the complex treatment of patients with refractory arterial hypertension.